NITROGEN OXIDES ABSORPTION INTO SODIUM HYDROXIDE SOLUTION IN A PACKED COLUMN COLUMN: EFFECT OF NAOH CONCENTRATION - Katima, J. H. Y.; Azapagic, A.; Handley, D. (Tanzania Journal of Engineering and Technology, 2018)
Abstract